2D/2D heterojunction of Ti3C2/g-C3N4 nanosheets for enhanced photocatalytic hydrogen evolution. Issue 17 (21st February 2019) - Su, Tongming; Hood, Zachary D.; Naguib, Michael; Bai, Lei; Luo, Si; Rouleau, Christopher M.; Ivanov, Ilia N.; Ji, Hongbing; Qin, Zuzeng; Wu, Zili
Abstract : The separation of photogenerated carriers and photocatalytic hydrogen production efficiency was greatly enhanced by the 2D/2D heterojunction of Ti3 C2 /g-C3 N4 . Abstract : Photocatalytic hydrogen evolution from water has received enormous attention due to its ability to address a number of global environmental and energy-related issues. Here, we synthesize 2D/2D Ti3 C2 /g-C3 N4 composites by electrostatic self-assembly technique and demonstrate their use as photocatalysts for hydrogen evolution under visible light irradiation. The optimized Ti3 C2 /g-C3 N4 composite exhibited a 10 times higher photocatalytic hydrogen evolution performance (72.3 μmol h −1 gcat −1 ) than that of pristine g-C3 N4 (7.1 μmol h −1 gcat −1 ). Such enhanced photocatalytic performance was due to the formation of 2D/2D heterojunctions in the Ti3 C2 /g-C3 N4 composites. The intimate contact between the monolayer Ti3 C2 and g-C3 N4 nanosheets promotes the separation of photogenerated charge carriers at the Ti3 C2 /g-C3 N4 interface. Furthermore, the ultrahigh conductivity of Ti3 C2 and the Schottky junction formed between g-C3 N4 /MXene interfaces facilitate the photoinduced electron transfer and suppress the recombination with photogenerated holes. This work demonstrates that the 2D/2D Ti3 C2 /g-C3 N4 composites are promising photocatalysts thanks to the ultrathin MXenes as efficient co-catalysts for photocatalytic hydrogen production.